2018
DOI: 10.22146/ijbiotech.35692
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 as a biomarker for ovarian cancer detection

Abstract: Ovarian cancer is a lethal disease. One of the problems faced by patients with ovarian cancer is the lack of symptoms in its early stages, which results in it only being detected when it is at an advanced stage. Therefore, there is an urgent need for biomarkers that can predict ovarian cancer precisely. The purpose of this study was to determine the expression of microRNA-21 as a predictive biomarker candidate in both early- and advanced-stage ovarian cancer. This was a cross-sectional study using the blood pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Involvement of miR-21 was reported in metastases and invasion in breast cancer via decrease in the expression of PTEN (Zhu et al 2008 (Lou et al 2010). A significant correlation of up-regulated miR-21 with FIGO stages was supported by Kartika et al (2018). Meng et al analyzed the expression of seven different microRNAs (miR-7, miR-16, miR-25, miR-93, miR-182, miR-376a and miR-429) with clinicopathological characteristics i.e., grading, lymph node and FIGO stages (Meng et al 2015).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Involvement of miR-21 was reported in metastases and invasion in breast cancer via decrease in the expression of PTEN (Zhu et al 2008 (Lou et al 2010). A significant correlation of up-regulated miR-21 with FIGO stages was supported by Kartika et al (2018). Meng et al analyzed the expression of seven different microRNAs (miR-7, miR-16, miR-25, miR-93, miR-182, miR-376a and miR-429) with clinicopathological characteristics i.e., grading, lymph node and FIGO stages (Meng et al 2015).…”
Section: Discussionmentioning
confidence: 85%
“…A number of other studies have highlighted the role of miR-21 in invasion and metastasis by targeting tumor suppressor genes including PTEN, BCL-2, and PDCD4 (Asangani et al 2008;Lou et al 2010;Chan et al 2014). Elevated levels of serum miR-21 in epithelial ovarian cancer patients have been reported (Xu et al 2013;Kartika et al 2018). It has been found that miR-22 regulates the BMP7 and PPAR alpha signaling pathways in human chondrocytes (Ting et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Early-diagnosis of EOC is difficult to achieve due to the asymptomatic nature of EOC at the early stage and lack of sensitive screening methods. Albeit, CA-125 is considered as the most promising biomarkers in serum, the sensitivity and specificity are not sufficient to detect cancer at an early stage ( 16 , 26 , 27 , 51 ). Less than half of the total cases of ovarian cancer are diagnosed effectively because of its limited specificity and sensitivity ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative miR-141 expression was calculated using 2 −ΔΔCt ( 49 51 ). The differences of copy number of miR-141 between the EOC group and healthy control group was calculated using the formula ΔΔCt miR-141 = (Ct miR-141−Ct miR-16) of EOC group-(Ct miR-141–Ct miR-16) of the healthy control group.…”
Section: Methodsmentioning
confidence: 99%